Women's Collectives and State-Led Development in West Bengal: Reimagining Selves During Counterinsurgency. (December 2020) - Kamra, Lipika
This article examines the micropolitics of state-directed women's collectives in India called self-help groups. Based on ethnographic fieldwork in a setting where development becomes a means of counterinsurgency for the state, it looks at how rural women in the eastern Indian state of West Bengal use these collectives to negotiate with the state and make claims on state actors. The article argues that rural women aspire to new individual selves through their membership of SHG collectives. Women reimagined their selfhoods through their access to the state-sponsored public sphere and building new roles for themselves within it. The argument is presented in conversation with research on self-help groups and microfinance initiatives for rural women, and it builds on work that examines the unintended consequences of such development interventions for women's lives.